On the spectrum of weakly almost periodic solutions of certain abstract differential equations - Aribindi Satyanarayan Rao; L. S. Dube (International Journal of Mathematics and Mathematical Sciences)
In a sequentially weakly complete Banach space, if the dual operator of a linear operator A satisfies certain conditions, then the spectrum of any weakly almost periodic solution of the differential equation u′=Au+f is identical with the spectrum of f except at the origin, where f is a weakly almost periodic function.